2016
DOI: 10.1139/bcb-2016-0010
|View full text |Cite
|
Sign up to set email alerts
|

A passenger strand variant in miR-196a2 contributes to asthma severity in children and adolescents: A preliminary study

Abstract: There is emerging evidence to support the role of microRNAs in allergic airway diseases and inflammation. Genetic variants in microRNA genes might affect microRNA-mediated cell regulation. This preliminary study was designed to investigate the association of the microRNA-196a2 rs11614913 (C/T) polymorphism with susceptibility to asthma and clinical outcomes in children and adolescents. Genotyping of rs11614913 polymorphism was determined in 96 patients with bronchial asthma (6-18 years of age) and 96 unrelated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…30 Some study in Egyptian population proposed that mir196a2 rs11614913 polymorphism could be associated with asthma severity. 31 Some of reports showed that polymorphism of mir196a2 rs11614913, as a biomarker associated with some types of cancer such as gallbladder, liver, breast, gastric, prostate, as well as autoimmune disease. 25 Based on the fact that genetic variants can alter the expression and function of miRNAs, we carried out an association study between miRNA polymorphism and MS susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…30 Some study in Egyptian population proposed that mir196a2 rs11614913 polymorphism could be associated with asthma severity. 31 Some of reports showed that polymorphism of mir196a2 rs11614913, as a biomarker associated with some types of cancer such as gallbladder, liver, breast, gastric, prostate, as well as autoimmune disease. 25 Based on the fact that genetic variants can alter the expression and function of miRNAs, we carried out an association study between miRNA polymorphism and MS susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…Patients were diagnosed according to the Global Initiative for Asthma (GINA) guidelines . Clinical examination was done for determining severity of the disease, therapeutic history and comorbidities . Asthmatic patients with chronic comorbidities, with manifestations of acute respiratory infection within 3 weeks, on systemic steroids within 2 weeks, or non‐compliant to treatment were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…PCRs were carried out in a 25‐μL reaction volume containing 12.5 μL 2 × Taqman ® genotyping Master Mix and 1.25 μL TaqMan ® SNP Genotyping Assay Mix (Thermo Fisher Scientific) with 40 ng genomic DNA. Real‐time PCR amplification was run on StepOne ™ Real‐Time PCR (Applied Biosystems) as previously described in details in our prior publication . Quality control measures included blinded analyses and replicates of 10% of samples with 100% concordance.…”
Section: Methodsmentioning
confidence: 99%
“…Bronchial asthma is a chronic heterogeneous respiratory disease that is characterized by airway inflammation, recurring bronchial obstruction, and airway hyper-responsiveness [ 1 , 2 ]. Most common histopathological features are inflammatory cell infiltration, sub-basement fibrosis, smooth muscle hypertrophy, mucus hypersecretion, injury to epithelial cells, and angiogenesis [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with anti-inflammatory drugs or bronchodilators usually improves some of these features. Nevertheless, therapeutic response relies on the interplay between environmental exposure and genetic background [ 2 ]. Despite several advances over the past decades in understanding the underlying mechanisms involved in the disease, there are no current satisfactory strategies for the cure or prevention of long-term decline in pulmonary function [ 5 ].…”
Section: Introductionmentioning
confidence: 99%